EVALUASI KEBIJAKAN DAN PRIORITAS PEMBANGUNAN DALAM UPAYA PENGUATAN EKONOMI MASYARAKAT - As’ari, Hasim; ', Zulkarnaini; Nasution, Mimin Sundari (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Policy Evaluation and Development Priorities in Efforts to Strengthen Economic Community. This study aimed to evaluate the implementation of economic development in an effort to strengthen society, find problems faced by the community in efforts to strengthen the economy, and finding the kinds of development that most prioritized in efforts to strengthen the local economy. This research was conducted in Rupat, as an area that includes regional, remote and outer (3T). The informants are North Rupat Head, head village of Teluk Rhu, head village of Pangkalan Nyirih, and several community leaders. Data collection technique was interview and observation. The data analysis is qualitative model from data collection, presentation of data, data reduction and conclusion. The results showed that the implementation of local development 3T still not up, there are still many problems faced by the people, either living as fishermen, farmers, and traders.